Two asymptotic models for arrays of underground waste containers - Allaire, G; Briane, M; Brizzi, R; Capdeboscq, Y (2009)
We study the homogenization of two models of an underground nuclear waste repository. The nuclear waste cells are periodically stored in the middle of a geological layer and are the only source terms in a parabolic evolution problem. The diffusion constants have a very large contrast between the fuel repository and the soil. It is thus a combined problem of homogenization and singular perturbation. For two different asymptotic contrasts we give the homogenized limit problem which is rigorously justified by using two-scale convergence. Eventually we perform 2D numerical computations to show the effectiveness of using the limit model instead of the original one. © 2009 Taylor and Francis.